The Influence of Motivational Training on Learning Achievement in Students - Amanda, Resi Suci; Rahni Rismawati; M Najarudin Rizki (CV. Era Digital Nusantara, 2024)
This research aims to examine the effect of motivational training on the academic achievement of psychology students at UIN Raden Fatah Palembang. A total of 30 students were selected using probability sampling techniques, and a pretest-posttest design was used in this research. The results show that motivational training does not have a significant effect in improving academic achievement. The pretest scores show a normal distribution, but the posttest scores are not normal. In addition, the correlation between pretest and posttest is very low. Therefore, further research is needed with a larger sample and different methods to validate the findings of this study.